Determinants Of Financial Statement Fraud Indications Using The Beneish M-Score Model In The Indonesian Infrastructure Sector - Zaen, Nadya Syahira; Fachriyah, Nurul (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2026)
This quantitative study aims to provide empirical evidence on the influence of earnings management, leverage, audit committee characteristics, and audit quality on financial statement fraud indicators, as measured by the Beneish M-Score model. Secondary data were collected from 55 infrastructure companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period, selected through purposive sampling, resulting in a final sample of 143 observations. Panel data regression using the Common Effect Model (CEM) was applied with EViews 13. The results show that earnings management positively affects financial statement fraud indications, the audit committee negatively affects these indications, while leverage and audit quality have no significant effect on financial statement fraud indications